2015
DOI: 10.1111/bjh.13600
|View full text |Cite
|
Sign up to set email alerts
|

Chronic neutrophilic leukaemia and plasma cell‐related neutrophilic leukaemoid reactions

Abstract: SummaryMany cases reported as 'chronic neutrophilic leukaemia' have had an associated plasma cell neoplasm. Recent evidence suggests that the great majority of such cases represent a neutrophilic leukaemoid reaction to the underlying multiple myeloma or monoclonal gammopathy of undetermined significance. We have analysed all accessible reported cases to clarify the likely diagnosis and to ascertain whether toxic granulation, D€ ohle bodies and an increased neutrophil alkaline phosphatase score were useful in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 65 publications
(105 reference statements)
5
54
0
Order By: Relevance
“…A favorable prognosis of MG-associated CNL has been previously noted by other investigators, and contrasts with that expected from true CNL [11]. This is consistent with the mounting evidence that CNL with a MG represents a plasma cell driven reactive process rather than a MPN [12]. This evidence includes spontaneous remissions of apparent CNL during treatment of the associated plasma cell proliferative disorder, the aberrant production of CSF3 by clonal plasma cells and the demonstration of polyclonal neutrophils in these cases [11,[13][14][15][16][17].…”
Section: Csf3r Mutations and Cnlsupporting
confidence: 89%
See 2 more Smart Citations
“…A favorable prognosis of MG-associated CNL has been previously noted by other investigators, and contrasts with that expected from true CNL [11]. This is consistent with the mounting evidence that CNL with a MG represents a plasma cell driven reactive process rather than a MPN [12]. This evidence includes spontaneous remissions of apparent CNL during treatment of the associated plasma cell proliferative disorder, the aberrant production of CSF3 by clonal plasma cells and the demonstration of polyclonal neutrophils in these cases [11,[13][14][15][16][17].…”
Section: Csf3r Mutations and Cnlsupporting
confidence: 89%
“…This evidence includes spontaneous remissions of apparent CNL during treatment of the associated plasma cell proliferative disorder, the aberrant production of CSF3 by clonal plasma cells and the demonstration of polyclonal neutrophils in these cases [11,[13][14][15][16][17]. It is recommended that evidence of a plasma cell dyscrasia be sought during the initial evaluation of suspected CNL, and if found, clonality of the neutrophil lineage should be confirmed before making this diagnosis [2,3,12,18]. Confirmation of CSF3R mutational status provides a new specific tool for this.…”
Section: Csf3r Mutations and Cnlmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, NLR can be present years before the diagnosis of carcinoma [5]. A few studies have reported that CNL or NLR can occur in plasma cell neoplasms [6,7].…”
mentioning
confidence: 99%
“…In addition, in CNL patients without the CSF3R T618I mutation, mutations in other genes such as ASXL1, TET2, SRSF2, JAK2, and SETBP1 have also been reported [3,7]. It would be helpful to examine the mutations mentioned above as well as the CSF3R T618I mutation to determine clonality, but we could not perform them.…”
mentioning
confidence: 99%